Kondisi Tutupan Terumbu Karang Keras dan Karang Lunak di Pulau Pramuka Kabupaten Administratif Kepulauan Seribu DKI Jakarta - Ardiansyah, Ekki Fikri; ., Hartoni; Litasari, Liliek (Maspari Journal : Marine Science Research, 2013)
Coral reef reaserch about cover condition of hard coral and soft coral in Pramuka Island Adminisratif Regency Seribu Island DKI Jakarta was conducted on november 2011. The purpose of this reasearch 1). to know persentage cover hard coral and soft coral 2). to analyzing the diversity, evenness and dominant of coral reefs 3). to know the parameters of the water temperature, current speed and current direction, brightness, salinity, pH, and TSS in the Pramuka Island Seribu Island. The reasearch method is used survey method, the determination of the stations point with the purposive sampling. Reef data retrieval using square transects at depths of 3 and 7 meters on 5 research stations. Identification of coral reefs using vidana program. Average conditions the percentage of coral cover on the Pramuka Island is 26,6%. Hard coral cover 6.0 to 34.8% at a depth of 3 meter and at 7 meter 9.3 to 49.5%. Soft coral cover only found at station 3 at a depth of 7 meter by 1.2% and at station 5 at a depth of 3 meter by 19.7%. Diversity of coral reefs as much as 43-55 colony genus/100m2. Coral reefs are dominated by the genus Montipora and Acropora. 0.34-0.92 coral mortality index showed the mortality rate ratio is high. Waters parameters such as temperature, current speed and current direction, brightness, salinity, pH, and TSS, which is a limiting factor in the Pramuka Island coral reefs are in the range of tolerances for coral reefs.Keywords: Coral Reef, Percentage of Coverage, Pramuka Island.